2013
DOI: 10.3892/or.2013.2902
|View full text |Cite
|
Sign up to set email alerts
|

Natural and glucosyl flavonoids inhibit poly(ADP-ribose) polymerase activity and induce synthetic lethality in BRCA mutant cells

Abstract: Poly(ADP-ribose) polymerase (PARP) inhibitors have been proven to represent superior clinical agents targeting DNA repair mechanisms in cancer therapy. We investigated PARP inhibitory effects of the natural and synthetic flavonoids (quercetin, rutin, monoglucosyl rutin and maltooligosyl rutin) and tested the synthetic lethality in BRCA2 mutated cells. In vitro ELISA assay suggested that the flavonoids have inhibitory effects on PARP activity, but glucosyl modifications reduced the inhibitory effect. Cytotoxici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 29 publications
4
45
0
Order By: Relevance
“…There seems to be a positive correlation between PARP activity and cytochrome C release. Interestingly, puerarin could mimic these inhibitory effects on PARP-1 because the ligand molecules of puerarin are well compatible with the active pocket of PARP-1 which is exhibited in a tight binding mode and the common molecular substructure of well known PARP-1 inhibitors, such as olaparib, can also be detected in puerarin [50][51][52]. And also, we identified that puerarin could partly inhibit the expression of PARP-1 and further disrupt the activation of NF-κB signaling pathway, reduce the generation of ROS and stabilize the function of mitochondria.…”
Section: Discussionmentioning
confidence: 96%
“…There seems to be a positive correlation between PARP activity and cytochrome C release. Interestingly, puerarin could mimic these inhibitory effects on PARP-1 because the ligand molecules of puerarin are well compatible with the active pocket of PARP-1 which is exhibited in a tight binding mode and the common molecular substructure of well known PARP-1 inhibitors, such as olaparib, can also be detected in puerarin [50][51][52]. And also, we identified that puerarin could partly inhibit the expression of PARP-1 and further disrupt the activation of NF-κB signaling pathway, reduce the generation of ROS and stabilize the function of mitochondria.…”
Section: Discussionmentioning
confidence: 96%
“…Luteolinidin may provide a greater preservation of the NAD(H) pool than a-NAD because the liposomal formulations used provide a much more potent inhibition of CD38 with good uptake throughout the heart. Alternatively, luteolinidin could exert some additional effects on inhibition of other pathways such as poly(ADP-ribose) polymerase, which has been shown to cause severe depletion of the myocardial NAD 1 pool in I/R (Pieper et al, 2000;Liaudet et al, 2001;Szabó et al, 2004;Geraets et al, 2007;Maeda et al, 2014;Boesten et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…At low concentrations, SBs induced by aflatoxin B1 (AFB1), methyl methanesulphonate (MMS), Dox, HgCl 2 or methyl mercury in HepG2 cells were decreased [100,101]. At high concentrations, quercetin and also rutin (glycoside of quercetin with rutinose) caused massive γ-H2AX foci, probably reflecting lethality [94], and yet they decreased DNA damage (SBs) induced by food mutagens PhIP and IQ [96]. …”
Section: Isolated Phytochemicalsmentioning
confidence: 99%